Misesian analysis of socialism: 100 years of correctness - Kavaliou, Aliaksandr V. (Journal of the Belarusian State University. Economics, 2023)
The article is devoted to the centenary of the publication of L. von Mises’ treatise «Socialism: an economic and sociological analysis», the significance of which lies in the study of the economic, political and ethical aspects of a socialist society. Emphasis is placed on the fact that L. von Mises derived an argument about the rational impossibility of the economic system of socialism from the main institutional provisions of this ideology (the abolition of private property of the means of production, the absence of a market as a mechanism for coordination and entrepreneurship), without which it is impossible to organise a full-fledged exchange of goods of a higher order and, consequently, obtain relevant market prices that carry information about the scarcity of goods and the most efficient methods of their production. In the absence of such information, the planning body is unable to determine the goods necessary for production. The analysis carried out by L. von Mises is not aimed exclusively at the form of socialism that was being realised at that time in Soviet Russia, but can be applied to any pseudo-socialist system or form of destructionism (from price regulation to compulsory unemployment insurance). The scientist demonstrated that political democracy, as a tool for non-violent change of power, corresponds to the system of private property, and under socialism it turns into authoritarianism.